2019
DOI: 10.3390/jcm8091344
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Sleep Bruxism, Stress, and Depression—A Polysomnographic Study

Abstract: Background and objectives: Sleep bruxism is a common phenomenon that can affect approximately 13% of adult population. It is estimated that bruxism can be caused by three types of factors: biological, psychological, and exogenous. There are many scientific reports about the coexistence of bruxism, stress, and psychoemotional disorders. The aim of this study is to evaluate the possible correlation between occurrence of sleep bruxism and perceived stress and depressive symptoms. Material and methods: The materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
1
45
0
4
Order By: Relevance
“…However, to date, the association between SB and inflammation remains unclear, and hence, the present paper addresses the need for investigating the inflammatory features of SB in order to bridge the gaps in the scientific literature. The association between stress and inflammatory markers has been well documented, 28 which suggests that SB, linked with psychoemotional components (such as emotional stress), 11,29,30 may also have an inflammatory etiology. Some authors have indicated that there is a lack of evidence on the association between SB and stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the association between SB and inflammation remains unclear, and hence, the present paper addresses the need for investigating the inflammatory features of SB in order to bridge the gaps in the scientific literature. The association between stress and inflammatory markers has been well documented, 28 which suggests that SB, linked with psychoemotional components (such as emotional stress), 11,29,30 may also have an inflammatory etiology. Some authors have indicated that there is a lack of evidence on the association between SB and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial factors, such as stress and anxiety, have been indicated as associated with both SB and AB [ 15 , 16 , 17 , 18 , 19 , 20 ]. However, the latest research showed that self-reported perceived stress was not correlated with the intensity of SB [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of cannabidiol and delta-9-tetrahydrocannabinol in an aerosol prescribed for oral use is estimated at 6%, and the delay of action is 120 min, much longer compared to the previously mentioned inhalation [36]. Due to the limited oral bioavailability [37] caused by digestion, the specificity of the location of MFP and the lipophilic nature of the test compound, it was decided to test transdermal CBD administration [1,4]. Transdermal drug formulations have many advantages over oral forms of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Bruxism is a common phenomenon that can affect from 8 to even 31% of the population without significant differences in relation to sex. Depending on the time of occurrence, we can distinguish awake bruxism (AB) and sleep bruxism (SB) [1]. AB is a masticatory muscle activity during wakefulness that is characterized by repetitive or sustained tooth contact and/or by bracing or thrusting of the mandible and is not a movement disorder in otherwise healthy individuals [2].…”
Section: Introductionmentioning
confidence: 99%